1994
DOI: 10.1093/jnci/86.2.110
|View full text |Cite
|
Sign up to set email alerts
|

A 190-Kilodalton Protein Overexpressed in Non-P-Glycoprotein-Containing Multidrug-Resistant Cells and Its Relationship to the MRP Gene

Abstract: Though associated with drug resistance, enhanced drug efflux, and decreased drug accumulation in cell lines, the role of this protein in clinical resistance has yet to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
1
2

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(75 citation statements)
references
References 0 publications
1
71
1
2
Order By: Relevance
“…Our in vitro studies utilised doses significantly below the IC 50 of doxorubicin for MCF-7 cells; concentrations were kept constant over a 10-day period to mimic the release characteristics from a liposomal carrier. In contrast to multistep exposure to doxorubicin, where either ABCB1 or ABCC1 is the dominant ABC transporter causing MDR (Shen et al, 1986;Barrand et al, 1994;Mehta, 1994), we show here that following single-step selection other transporters, including ABCC4 and ABCG2, are overexpressed. Importantly, ABCG2 was found to confer resistance to doxorubicin in breast, ovarian and colon cancer cell lines.…”
contrasting
confidence: 77%
See 1 more Smart Citation
“…Our in vitro studies utilised doses significantly below the IC 50 of doxorubicin for MCF-7 cells; concentrations were kept constant over a 10-day period to mimic the release characteristics from a liposomal carrier. In contrast to multistep exposure to doxorubicin, where either ABCB1 or ABCC1 is the dominant ABC transporter causing MDR (Shen et al, 1986;Barrand et al, 1994;Mehta, 1994), we show here that following single-step selection other transporters, including ABCC4 and ABCG2, are overexpressed. Importantly, ABCG2 was found to confer resistance to doxorubicin in breast, ovarian and colon cancer cell lines.…”
contrasting
confidence: 77%
“…Although doxorubicin can work through various mechanisms, it is still not immune to the MDR phenotype and, consequently, the development of resistance to doxorubicin has been well documented in a broad range of cell lines (Shen et al, 1986;Barrand et al, 1994;Mehta, 1994). To more closely examine the regulation of ABC transporter expression at concentrations similar to those in vivo, we established several single-step doxorubicin-selected clones with three different cancer cell lines and found that these clones did not express ABCB1 (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Another form of multidrug resistance is non-Pgp-mediated multidrug resistance. This type of multidrug resistance has been reported in doxorubicin-selected lung carcinoma cell lines (Mirski et al, 1987;Scheper et al, 1993;Barrand et al, 1994) and a leukaemia cell line (Marsh et al, 1987) among others. Expression of a 190 kDa vesicular glycoprotein (Krishnachary et al, 1993) and a 110 kDa membrane glycoprotein (Scheper et al, 1993) appears to be associated with the non-P-gp-mediated multidrug resistance in some of these cell lines.…”
mentioning
confidence: 64%
“…42,43 MRP1 has shown to be expressed in many non-Pgp/ MDR1 cell lines. 44,45 MRP1 transfection experiments, however, did not confer resistance to cisplatin. 44 Using the NCI 60 drug screening cell lines, Fojo et al 46,47 demonstrated a positive correlation between MDR1/MRP1 gene expression level and chemical compound sensitivity.…”
Section: Mrp1 Mrp2mentioning
confidence: 87%